Formação de leitores adultos com escolarização irregular e extemporânea - Luciana Prazeres Silva (2003)
The conditioning factors of four adult readers with irregular and extemporaneous schooling were analysed on this master’s degree dissertation. These people were students from the elementary school in a course for adults offered by UFMG. A semi-structured interview was used to get information about these people’s journey. Firstly, a narration about each one was written. Then an analysis was made to compare the adult readers. It’s possible to say that the adult readers formation with irregular and extemporaneous schooling can not be related to only one factor. Then we tried to understand the factor interdependences and this allowed us to see the uniqueness of each case. The familiarization, schooling, self education, worh market insertion and social movement participation were the interdependent conditioning factors that were more showed on the four analysed journey.